Health Economic Evaluations of Hip and Knee Interventions in Orthopaedic Sports Medicine: A Systematic Review and Quality Assessment. Issue 3 (9th March 2021) - Primeau, Codie A.; Zomar, Bryn O.; Somerville, Lyndsay E.; Joshi, Ishita; Giffin, J. Robert; Marsh, Jacquelyn D.
Background: The economic burden of musculoskeletal diseases is substantial and growing. Economic evaluations compare costs and health benefits of interventions simultaneously to help inform value-based care; thus, it is crucial to ensure that studies are using appropriate methodology to provide valid evidence on the cost-effectiveness of interventions. This is particularly the case in orthopaedic sports medicine, where several interventions of varying costs are available to treat common hip and knee conditions. Purpose: To summarize and evaluate the quality of economic evaluations in orthopaedic sports medicine for knee and hip interventions and identify areas for quality improvement. Study Design: Systematic review; Level of evidence, 3. Methods: The Medline, AMED, OVID Health Star, and EMBASE databases were searched from inception to March 1, 2020, to identify economic evaluations that compared ≥2 interventions for hip and/or knee conditions in orthopaedic sports medicine. We assessed the quality of full economic evaluations using the Quality of Health Economic Studies (QHES) tool, which consists of 16 questions for a total score of 100. We classified studies into quartiles based on QHES score ( extremely poor quality to high quality ) and we evaluated the frequency of studies that addressed each of the 16 QHES questions. Results: A total of 93 studies were included in the systematic review. There were 41 (44%) cost analyses, of which 21 (51%) inappropriately concluded interventions were cost-effective. Only 52 (56%) of the included studies were full economic evaluations, although 40 of these (77%) fell in the high-quality quartile. The mean QHES score was 83.2 ± 19. Authors consistently addressed 12 of the QHES questions; questions that were missed or unclear were related to statistical uncertainty, appropriateness of costing methodology, and discussion of potential biases. The most frequently missed question was whether the cost perspective of the analysis was stated and justified. Conclusion: The number of studies in orthopaedic sports medicine is small, despite their overall good quality. Yet, there are still many highly cited studies based on low-quality or partial economic evaluations that are being used to influence clinical decision-making. Investigators should follow international health economic guidelines for study design and critical appraisal of studies to further improve quality.